Supramolecular self-assembled ruthenium-polypyridyl framework encapsulating discrete water cluster - Deshpande, Megha S.; Kumbhar, A. S.; Puranik, Vedavati G.; Selvaraj, K. (Crystal Growth & Design, 2006)
Keywords: 4; 4 `-dimethoxydiphenylmethane; benzylsulfonic acid; Condensation of anisole; p-formaldehyde; Zr-TMS-BSA

Hydrogen bonding-directed metallosupramolecular structural motifs based on a peripheral urea fused bipyridine tecton - Deshpande, Megha S.; Kumbhar, Avinash S.; Puranik, Vedavati G. (Crystal Growth & Design, 2008)
The potential of bipyridine glycoluril (BPG), a urea fused bipyridine, tecton to form metal-organic frameworks (MOFs) has been explored by structural characterization of BPG and its complexes [Ru(phen)(BPG)(2)]Cl(2) (1) and [Ru(BPG)(3)]Cl(2) (2). The single crystal X-ray structure of BPG reveals that the inherent H-bond donor (N-H) and acceptor groups (C=O) exhibit a potential to generate diverse supramolecular motifs depending on the stoichiometry of tectons. The single crystal X-ray analysis of the secondary building units 1 and 2 provide evidence for this hydrogen-bonding capacity which results in supramolecular self-assembled metal-organic frameworks (MOF) via C-H center dot center dot center dot Cl, C-H.center dot center dot center dot O, N-H center dot center dot center dot Cl, and N-H center dot center dot center dot O interactions with a cluster of water molecules and chlorine anions surrounding secondary building units in I and channels encapsulating mixed water-dimethylsulfoxide clusters in 2.